The Effect of Anthropometric Training on the Knowledge of Integrated Health Post (Posyandu) Cadres in Pulau Kelapa Village, Seribu Islands - Wijayanti, Wiwit; Dwiyana, Parlin; K, Slamet Santoso; Salsabila, Dhea Marliana (LPPM Universitas Mohammad Husni Thamrin, 2025)
Community health volunteers (Posyandu cadres) play a pivotal role in the implementation of community-based health services. Their active involvement is expected to enhance family and community participation (Nurbaya et al., 2022). Adequate knowledge and technical skills are essential for conducting accurate anthropometric measurements among children under five years of age. Kelapa Village is identified as a stunting locus in the Kepulauan Seribu Regency; therefore, Posyandu cadres involved in anthropometric data collection require structured training to improve their competencies. This study aimed to analyze the effect of anthropometry training on the knowledge of Posyandu cadres in Kelapa Village. A one-group pretest–posttest design was employed to assess changes in cadres’ knowledge before and after the anthropometry training. The study population comprised all Posyandu cadres in Kelapa Village, North Kepulauan Seribu District (n = 34). Total sampling was applied. The results of the analysis on the effect of anthropometric training on the knowledge of Posyandu cadres in Kelapa Subdistrict, using a dependent t-test, showed that the mean knowledge score at the pre-test was 65.53 with a standard deviation of 8.44. At the post-test, the mean knowledge score increased to 73.71 with a standard deviation of 9.05. Furthermore, 60 days after the intervention, the mean knowledge score further increased to 83.41 with a standard deviation of 14.32. The p-value was < 0.001, indicating a statistically significant difference in knowledge levels before and after the training. These findings suggest that anthropometric training effectively improves the knowledge of Posyandu cadres. Therefore, regular monitoring by the Primary Health Center (Puskesmas) is recommended to ensure that field practices are consistently implemented in accordance with established standards.